Study on "Aspin Bubbles" and Gravitational Deflection - Lana-Renault, Yoël (Fundamental Research and Application of Physical Science Vol. 1, 2023)
We will show that the gravitational deflection can be approached as a simple refraction of light through space, and that this depends at all times on the "scalar" gravity existing in said space. Based on the "Aspin Bubbles" theory, we propose a velocity function v(r) for light that is exclusively dependent on the gravity g(r) that exists at each point P(r) of space, and with which, by applying the laws of refraction, the gravitational deflections of light measured up to this point are obtained. Consequently, we obtain a gravitational index of refraction ng for each point P(r) of the space and conclude that our space is probably not curved but rather straight or apparently curved by the gravitational fields that refract light.